Internal and External Quality Assurance System in Private Islamic Religious Colleges: A Case Study of the Implementation of the PEPPP Cycle at Ma'arif University, Lampung - Nurani Nurani; Agus Pahrudin; Yuberti Yuberti; Achi Rinaldi (Assyfa Journal of Islamic Studies, 2026)
The implementation of the Internal Quality Assurance System (SPMI) at Private Islamic Religious Higher Education Institutions (PTKIS) often faces challenges such as a weak quality culture, inconsistent follow-up, and the perception that accreditation is merely administrative. Furthermore, digitalization through the Sapto 2.0 platform has given rise to new shortcomings: reliance on a manual reminder approach in reporting lecturer grades, gaps in data markup in Student Lecture Activity (AKM) reports, and inconsistencies in the Semester Credit Unit (SKS) system during accreditation. This study aims to analyze the implementation of SPMI and responses to external quality assurance at Ma'arif University, Lampung, with a focus on the PPEPP cycle (Determination, Implementation, Evaluation, Control, Improvement). A qualitative case study approach was used. Data were collected through in-depth interviews with 10 informants (leaders, Head of LPM, heads of study programs, lecturers, and educational staff), documentation studies, and observations. The results indicate that structurally, SPMI is implemented through an annual PPEPP cycle that produces a measurable follow-up plan. However, three critical deficiencies were found: (1) the practice of marking up AKM data prior to accreditation due to target pressures and system weaknesses, (2) inconsistencies in recording credits between RPS and transcripts due to unvalidated data migration, and (3) the lack of connection between the internal quality reporting system and the graduate tracer study. The response to external quality assurance (LAMDIK assessment) provided a moment for reflection, but without transparent digital improvements, the synergy between SPMI and SPME remains vulnerable to administrative manipulation. It was concluded that continuous quality improvement in PTKIS requires a reliable electronic quality assurance system, with an audit trail, and integrated with the tracer study, not just an annual cycle formality.